2000
DOI: 10.1046/j.1365-2052.2000.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the causal mutation for canine leukocyte adhesion deficiency (CLAD) using pyrosequencing

Abstract: A missense mutation in the ITGB2 gene causes canine leukocyte adhesion deficiency (CLAD) in Irish setters. We constructed a diagnostic test to identify heterozygous CLAD carriers based on a newly developed technology termed pyrosequencing. Although primarily designed for high-speed generation of DNA sequence in a gel-free system, the technology can be applied to rapid single-nucleotide polymorphism analysis in a clinical setting. The testing of 339 dogs originating from a total of 10 countries was conducted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
1
19
2
2
Order By: Relevance
“…The frequency of 11% was significantly less than Kijas et al. (2000) reported, who observed the frequency of CLAD among the Irish setters to be 21%.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…The frequency of 11% was significantly less than Kijas et al. (2000) reported, who observed the frequency of CLAD among the Irish setters to be 21%.…”
Section: Resultscontrasting
confidence: 61%
“…Concerning investigations from Kijas et al. (2000) they concluded that the CLAD allele was widespread, with frequencies ranging from 0.03 to 0.27.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason BLAD is one of the worst inherited diseases, threatening the dairy industry of the USA and the whole world. BLAD cases have already been reported in many European countries, Australia, South and North America, and India (Gilbert et al, 1993;Zsolnai and Fésüs, 1996;Muraleedharan et al, 1999;Kijias et al, 2000).…”
mentioning
confidence: 99%
“…At this time FLAD seems to be a rare immunodeficiency in cats with the ITGB2 mutation being isolated and not widespread. In contrast, the mutant alleles in Holstein cattle and Red and White Setters were relatively common with worldwide occurrence, and screening programs have successfully reduced the occurrence of BLAD and CLAD.…”
Section: Discussionmentioning
confidence: 99%